Rancang Bangun Mesin Perontok Sawit Kapasitas 150 Kg/Jam - Nural Fajri; Sigit Kurniawan; Sepriyanto (ABEC Indonesia, 2023)
This threshing process is carried out so that small palm fruit or oil palm fruit bunches weighing under 5 kg can be accepted at the palm oil mill. In general, fresh fruit bunches (FFB) weighing under 5 kg are not sold, so before being brought to the palm oil mill, they must be threshed first so that the palm becomes loose or granules that can be accepted by the palm oil mill. Designing a model of a palm fruit threshing machine from the bunches aims to increase profits for palm oil entrepreneurs, because small palm fruit can be accepted in palm oil mills. In this design, the thresher model is made, the engine uses a diesel motor, WPA 60 1:40 gearbox, rubber clutch and the capacity of this palm thresher machine is 150 kg/hour. Testing of the palm thresher machine is carried out in three types of tests, the results of production capacity and fuel use. The production capacity of palm fruit obtained is 324.6 kg/hour while the use of fuel is 900 ml/hour